The Influence of Business Environment on Entrepreneurial Behavior through Motivation and Competitive Advantage as Mediators - Iskandar, Iskandar; Yulia Rianawati,; Novi Satria Pradja,; Entin Jumantini,; Sri Mulyati, (Jurnal Entrepreneur dan Entrepreneurship, 2024)
This study aims to determine whether entrepreneurial motivation and competitive advantage mediate the influence of the business environment on entrepreneurial behavior. The method used is survey. The data analysis technique used is to use a parallel multiple mediator model. The sample in this study were all owners of digital-based SME in Majalengka Regency, totaling 43 SME. The results show that the business environment has a positive effect on entrepreneurial behavior. Entrepreneurial motivation mediates the effect of the business environment on entrepreneurial behavior, in which the business environment is significant to entrepreneurial behavior, after being mediated by entrepreneurial motivation. Competitive advantage mediates the influence of the business environment on entrepreneurial behavior, in which the business environment is significant to entrepreneurial behavior, after being mediated by competitive advantage. The mediation is known as the partial mediation.